Organizatsiya trenirovochnogo protsessa v god glavnykh sorevnovanii - Rubin, V. S. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The aim of this study was to substantiate the strategy of training loadings at the final year of the olympic cycle in elite hurdlers training. The data of training loading in 110 m hurdle runners at two last years of the olympic cycle (n=15) had been analysed.